The criminal liability of legal persons in Colombia. Problems about its application since the issuance of the Penal Code - Missas Gómez, Jorge Eduardo (2018)
Currently legal in the world requires the development of public policies in criminal matters, whose origin is social, cultural, political and economic phenomena. This reality implies the emergence of criminal phenomena which include, beyond the natural person, organizations capable of being subjects of law in the civil field and in the criminal field. This relation is valid in the light of the regulatory provisions established by civil legislation and recently the sanctions imposed on the various undertakings crimes. Therefore, it is necessary to analyze the legal reality that presents the criminal responsibility of collective entities and establish whether the Colombian legal system considers controls and penalties that may be imposed on legal persons.